Influence of motivated walking with partial body weight supporting on the gross motor functions in children with cerebral palsy - O.B. Nekhanevych; V.B. Bakuridze-Manina; O.L. Smirnova; Y. Byoung-Yul; O.V. Kosynskyi (Medičnì Perspektivi)
The aim of the work is to increase the effectiveness of physical therapy of gross motor functions impairments in children with spastic cerebral palsy by using a therapeutic exercises program with partial body weight supporting and motivated walking on the device for the rehabilitation of people with impaired functions of the musculoskeletal system. The study included 30 children 6 to 11 years old with a spastic form of cerebral palsy. All patients were divided into 2 groups: in group I, in addition to the standard complex of physical therapy, walking according to the dynamic method was prescribed, in group II – according to the static method with partial body weight supporting. The duration of the program was 6 weeks. The survey was carried out before the start, at 2, 4 and 6 weeks of therapy. We studied the spatiotemporal characteristics of walking and activity of daily living indicators. The use of the developed program with the rehabilitation device positively influenced the spatiotemporal indicators of walking in both groups. The stride length, walking speed and the length of the covered distance increased statistically significantly. A significant increase in the volume of performed activities of daily living in the I group was found. At the same time, an increase in this indicator was also observed in group II, but it did not reach statistical significance. The use of the developed program of therapeutic exercises, including walking with motivated movement and partial body weight supporting on the developed rehabilitation device positively influenced the static and dynamic characteristics of walking, which improved the performance of activities important for children with cerebral palsy, especially walking and running. The optimal time for increasing the stride length is a 4-week program, for the development of general endurance and speed – a 6-week program of therapeutic training.